If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3(2a-6)-3(8-5a)=48
We move all terms to the left:
-3(2a-6)-3(8-5a)-(48)=0
We add all the numbers together, and all the variables
-3(2a-6)-3(-5a+8)-48=0
We multiply parentheses
-6a+15a+18-24-48=0
We add all the numbers together, and all the variables
9a-54=0
We move all terms containing a to the left, all other terms to the right
9a=54
a=54/9
a=6
| 1.28=x-54/17 | | 2/3-6x^-2=0 | | -5+3y=-2 | | 128=-8(8v-8) | | 4x+35=-3 | | 4b+19=3 | | 82=2(7n-1) | | -6(-4+7v)=-144 | | 90=6(6+3m) | | 12x-115=-6x+155 | | -3(x-14=42 | | /3+2.7x=9.6+3.2x | | 1+8(1+2p)=-103 | | 3x÷4-1=-7 | | 3x²/6=81 | | -6.1-n=-3.3 | | p-4/3=2 | | c/9=-5 | | 3x^2/6=81 | | 7(m+4)+7m=140 | | y/3+8y/5-3/6=y+7/2 | | 3z÷7+8=-3 | | f=930/5+32 | | x+18÷2=x×5 | | -.52=x-52/15 | | 28(z-28)=30z | | 8n-2n=20 | | -6.9552=-3.312x | | 10x-24=17x+16 | | 0.625=75/x | | -26.1=-6.9+n | | 3(x-5)-2(x+7)=x |